2013
DOI: 10.1093/eurjhf/hfs153
|View full text |Cite
|
Sign up to set email alerts
|

Association between diabetes mellitus and post‐discharge outcomes in patients hospitalized with heart failure: findings from the EVEREST trial

Abstract: AimsWe evaluated the impact of diabetes mellitus (DM) and diabetic therapy on outcomes in patients with reduced ejection fraction (EF) after hospitalization for heart failure (HF). DM is prevalent in patients hospitalized with HF, yet inconclusive data exist on the post-discharge outcomes of this patient population. Methods and resultsPost-hoc analysis was performed on the EVEREST (Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study with Tolvaptan) study, a randomized trial of patients hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
1
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(149 citation statements)
references
References 33 publications
6
127
1
15
Order By: Relevance
“…N.S. had full access to all the data in the study and takes mellitus 24 have high morbidity and mortality despite current therapy, the MR may be an important therapeutic target in these vulnerable patients. ARTS-HF Japan was a small study designed to test the response to finerenone in Japanese patients.…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…N.S. had full access to all the data in the study and takes mellitus 24 have high morbidity and mortality despite current therapy, the MR may be an important therapeutic target in these vulnerable patients. ARTS-HF Japan was a small study designed to test the response to finerenone in Japanese patients.…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…30 Another study revealed that 33% of all HF patients have concomitant DM and this number rises up to 40% in patients admitted with acute decompensated HF. 31 Sarma S et al 32 showed approximately 40% of hospitalized HF patients with low EF have DM. DM in hospitalized patients is associated with worse prognosis 32 , increased risk for combined CV mortality and HF-related hospitalization 33 , and longer hospital stay 31 , despite receiving care that is similar to that for patients without DM 34 although this paradigm is not a consistent finding.…”
Section: Discussionmentioning
confidence: 99%
“…31 Sarma S et al 32 showed approximately 40% of hospitalized HF patients with low EF have DM. DM in hospitalized patients is associated with worse prognosis 32 , increased risk for combined CV mortality and HF-related hospitalization 33 , and longer hospital stay 31 , despite receiving care that is similar to that for patients without DM 34 although this paradigm is not a consistent finding. Anaemia is also a common companion to diabetes and this is because of the high prevalence of chronic kidney disease in patients with diabetes, leading to functional erythropoietin deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…22 The diagnosis of diabetes in heart failure patients results in increased cardiovascular mortality, higher readmission rates 23 and increased hospital lengths of stay. 24 Data from ALLHAT (The Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial) demonstrated significantly higher risk for heart failure admissions or death in diabetics, nearly twice as high than in those patients without diabetes.…”
Section: Outcomes In Heart Failure With Concomitant Diabetesmentioning
confidence: 99%